Discrimination of Urban Spaces with Different Level of Restorativeness Based on the Original and on a Shorter Version of Hartig et al.’s Perceived Restorativeness Scale - Negrín, Fátima; Hernández-Fernaud, Estefanía; Hess, Stephany; Hernández, Bernardo (Frontiers in Psychology, 2017)
Restorativeness is defined as the potential of the environment to re-establish certain cognitive capacities related to human information processing. The most frequently used instrument for evaluating the restorativeness of places is the Perceived Restorativeness Scale, proposed by Hartig and colleagues (1991). Later on, shorter versions of the Perceived Restorativeness Scale were proposed. The aim of this work is to evaluate the discriminatory capacity of the original and of a shorter Spanish version of the PRS, considering urban settings previously selected for having different level of restorativeness, according to expert’s criteria. The study involved 244 students and used a 3 x 2 mixed experimental design, with two independent variables: Restorativeness of a place (between-subjects), which was manipulated by showing pictures of settings selected with varying levels of restorativeness (high, medium, low), and length of the scale (within-subjects), which was manipulated by asking subjects to fill in both the original and a shorter version of the PRS. The order of presentation of the two scales was counterbalanced. Results show an appropriate reliability for both version of the scale. Items of being-away, fascination, and coherence of the shorter scale correlate more strongly with the corresponding factor of the original scale, compared to the others factors. Both scales produce similar values for the perceived restorativeness of the different places, except for places with low restorativeness.